2008
DOI: 10.1167/iovs.08-1987
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Separation of Two Distinct Populations of Mouse Corneal Epithelial Cells with Limbal Stem Cell Characteristics by Centrifugation on Percoll Gradient

Abstract: These findings demonstrate the presence of two distinct populations of corneal epithelial cells with limbal SC characteristics, based on differential expression of the keratin-specific marker K12 and transcription factor p63, and suggest a difference in developmental stage of the two populations, with the K12(-)p63(+) population being closer to the primitive limbal SC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…The appearance of α-actin and vimentin in epithelial cells marks a pathological state of metaplasia. Our immunocytochemistry study on limbal epithelial cells showed staining for ABCG2, p63 and LGR5, which confirms previously published data (10,11) and confirms that they can be used as identifying markers for adult limbal stem cells. Our results show that a proportion of isolated human corneal epithelial cells possess limbal stem cell markers, indicating that these cells were still able to maintain the corneal limbal stem cell phenotype following cell isolation.…”
Section: Discussionsupporting
confidence: 91%
“…The appearance of α-actin and vimentin in epithelial cells marks a pathological state of metaplasia. Our immunocytochemistry study on limbal epithelial cells showed staining for ABCG2, p63 and LGR5, which confirms previously published data (10,11) and confirms that they can be used as identifying markers for adult limbal stem cells. Our results show that a proportion of isolated human corneal epithelial cells possess limbal stem cell markers, indicating that these cells were still able to maintain the corneal limbal stem cell phenotype following cell isolation.…”
Section: Discussionsupporting
confidence: 91%
“…Conceptually, they may form a component of the molecular mechanisms by which long-lived stem cells reduce the potential for genomic damage over their extended lives, and their expression has been correlated with stem cell activity [90] . ABCG2 expression in the limbus is one such example and cells expressing this marker can be isolated as a "side population" by fluorescenceactivated cell sorting (FACS) [3,57,[91][92][93][94][95] . However, as noted above, some of the ABCG2-positive, labelretaining cells with a high nucleus to cytoplasm ratio cells in the rat limbus have been identified as Langerhans cells rather than epithelial stem cells [56] .…”
Section: Stem Cell Markers and Phenotypementioning
confidence: 99%
“…A single-cell suspension from limbal tissues was obtained by enzyme digestion, as we have described [24]. In brief, limbal tissues (a narrow tissue between the cornea and the conjunctiva) from 10-12 BALB/c mice were cut out with scissors and subjected to 10 short (10 min each) trypsinization cycles.…”
Section: Preparation Of a Single-cell Suspension From Limbal Tissuementioning
confidence: 99%